Incentivizing Calculated Risk-Taking : Evidence from an Experiment with Commercial Bank Loan Officers - Cole, Shawn; Kanz, Martin; Klapper, Leora (World Bank, Washington, DC, 2012)
This paper uses a series of experiments with commercial bank loan officers to test the effect of performance incentives on risk-assessment and lending decisions. The paper first shows that, while high-powered incentives lead to greater screening effort and more profitable lending, their power is muted by both deferred compensation and the limited liability typically enjoyed by loan officers. Second, the paper presents direct evidence that incentive contracts distort judgment and beliefs, even among trained professionals with many years of experience. Loans evaluated under more permissive incentive schemes are rated significantly less risky than the same loans evaluated under pay-for-performance.